Political economy of special economic zones location in Poland - Cieślik Andrzej (Journal of Economics and Management, 2025)
– This article’s main objective is to empirically assess the role of political representation in determining the spatial location of special economic zones (SEZs) in Poland in the late 1990s. In particular, we test the main hypothesis, postulating that the location of SEZs was more likely to occur in regions with a stronger political representation of the ruling party.